Village Funds and Corruption Tendencies in Village Development - Yulfani, Yulfani; Parwati, Ni Made Suwitri; Tanra, Andi Ainil Mufidah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This study aims to analyze the effect of village funds and the tendency of corruption on village development in Central Sulawesi Province. This study uses village government data in Central Sulawesi Province. Using the Proposive Sampling method for sample selection, so that the total final sample obtained was 1,840 observations. The results showed that village funds and corruption tendencies had an impact on increasing the village development index (IDM). Related to the existence of control variables, the characteristics of the village head and village characteristics also show an influence on increasing IDM. This research has implications for the importance of supervision and efforts to eradicate corruption at the village level to increase IDM